Enhanced disinfection efficiency using Cu vortex diode for providing safe drinking water: devising newer methodologies - Dixit, Divya; Balapure, Kshama; Bhandari, Vinay M. (Environmental Quality Management, 2024)
The present research aims to refine the hydrodynamic cavitation technique with traditional knowledgebase of Ayurveda for more efficient water disinfection and that has huge potential for implementation in real life, especially for substituting the existing chlorination method for drinking water treatment. The study incorporates use of newer copper reactor configuration, employing vortex flow for generating cavitation for the disinfection of water. Elimination of model contaminant, Escherichia coli, with initial concentration of ∼105 CFU/mL of bacteria was used for the disinfection study. Copper vortex diode with a capacity of 1 m3/h was employed as a cavitating device. The cavitation using copper vortex diode gave significantly higher disinfection, over 30%, compared that with conventional vortex diode, with aluminum as material of construction, under similar conditions. Remarkably, the addition of 0.1% betel leaf oil led to an extraordinary 260-fold increase in the rate of disinfection, requiring only a single pass to achieve complete bacteria elimination. Furthermore, a notably high synergistic index of 246.96 was achieved for the process intensification approach using the Cu vortex diode. The cost was substantially reduced by approximately three times to 0.011 $/m3 using the Cu vortex diode compared to the conventional vortex diode. The developed strategy offers significantly enhanced performance, as well as a techno-economical and sustainable solution for drinking water treatment to ensure the provision of safe drinking water. Moreover, the newer methodology can have the advantage of producing no harmful carcinogenic disinfection by-products compared to chemical disinfection processes apart from sustainable alternative to chlorination.